The Effect of Employee Competence and Work Motivation on the Quality of Financial Reporting: JEL Classification: M41, M12, J24, H83, D73 - Irawati M; Abdul Samad Arief; Mujahid Yunus (Journal La Bisecoman, 2026)
This study aims to determine whether employee competence and work motivation have an influence on the quality of financial reporting at the Office of the Airport Authority Region V Makassar. The data in this research were obtained through the distribution of questionnaires as the primary instrument. The sampling technique used was the saturated sample method, where all members of the population were used as the research sample. Prior to its use, the research instrument was tested for validity and reliability, and also underwent classical assumption tests such as normality, multicollinearity, and heteroscedasticity. The data were analyzed using multiple linear regression with the help of statistical software. The results of the study indicate that employee competence has a positive influence on the quality of financial reporting. This means that the higher the level of employee competence in carrying out tasks related to the preparation of financial reports, the better the quality of the reports produced. The competencies in question include understanding financial regulations, accuracy, and technical skills in preparing reports accurately and on time. In addition, work motivation also contributes positively to the quality of financial reporting. Employees with high levels of motivation tend to be more responsible and committed to completing their tasks, including in the preparation of financial reports. Together, employee competence and work motivation significantly influence the improvement of financial reporting quality, although other external factors not examined in this study may also have an impact.